XPS spectra as a tool for studying photochemical and thermal degradation in APbX3 hybrid halide perovskites. (January 2021) - Zhidkov, Ivan S.; Boukhvalov, Danil W.; Akbulatov, Azat F.; Frolova, Lyubov A.; Finkelstein, Larisa D.; Kukharenko, Andrey I.; Cholakh, Seif O.; Chueh, Chu-Chen; Troshin, Pavel A.; Kurmaev, Ernst Z.
Abstract: This article features the potential and examples of the comprehensive use of X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) to analyze the degradation processes in A Pb X 3 hybrid halide perovskites, where the X -site anion is I – and Br – and the A -site cation is represented by CH3 NH3, CH(NH2 )2, and Cs. The whole set of XPS options is used, including the measurements of survey, core levels (C 1s, N 1s, Pb 4f, I 3d and Br 3d), and valence bands spectra, which provides a complementary understanding of the electronic structure and chemical bonding of perovskites while excluding the random errors. It is found that stability of A Pb X 3 perovskites with respect to light soaking and heat stress is connected with the formation of Pb X 2 degradation product, which can be monitored by high-energy resolved XPS Pb 4f, I 3d-spectra and valence band spectra. The obtained results are confirmed by DFT calculations of the formation energies of intrinsic Pb X 2 -defects. Furthermore, our results show that the resistance of hybrid lead halide perovskites to stress factors (light or heat) is gradually increased while substituting the A -site cation going from CH3 NH3 + to CH(NH2 )2 + and then to Cs + . Graphical Abstract: ga1 Highlights: Intrinsic photochemical and thermal stability of a series of lead halide perovskites was investigated. Combination of XPS spectra and DFT studies were used to analyze the degradation processes in lead halide perovskites. Mechanism of degradation of hybrid perovskites in connection with formation of intrinsic Pb X 2 -defects was revealed. Resistance of A Pb X 3 perovskites to light and heat is increased while substituting the A -cation from CH3 NH3, CH(NH2 )2, to Cs.